WASTEWATER SPECIFIC EMISSION FACTOR FROM COMMUNAL WASTEWATER TREATMENT PLANT (WWTP) - Reni Nuraeni; Amallia Ashuri (Pusbindiklat - LIPI, 2018)
Greenhouse gasses (GHG) that produced by anaerobic digestion of wastewater consists of CH4 gas and NO2 gas. Beside the data of specific activity, the specific emission factor also plays important part to determinate GHG emission. The aim of this paper is to know specific emission factor value from communal wastewater treatment plant (WWTP), as an input to determinate GHG emission for determination of GHG emission reduction rate. The data was collected by taking sample of BOD, CH4 gas, and CO2 gas from communal WWTPs. Sampling location were communal WWTPs in Jakarta City, Bandung City, and Yogyakarta City. Those WWTPs using anaerobic baffle reactor as their treatment system with capacity varied between 40-200 EP. The parameters were BOD and CH4 that measured using grab sampling in the morning and evening. Data analyzed by quantitative methods. The specific emission factor value was determined from CH4 gas measurement which affected by wastewater treatment unit dimension, gas catcher chamber, and air suction pump capacity. The analysis results showed specific emission factor for communal WWTPs from the three cities is 0.00171 kg CH4/kg BOD. The value has bid difference when compared to IPCC’s default that is 0.48 kg CH4/kg BOD. This is due to the formation of CH4 gas and CO2 gas was strongly influenced by environmental condition in real time condition. This factor is not taken into consideration in IPCC’s default.